Microwave processing: A way to reduce the anti-nutritional factors (ANFs) in food grains. (October 2021) - Suhag, Rajat; Dhiman, Atul; Deswal, Gaurav; Thakur, Dhruv; Sharanagat, Vijay Singh; Kumar, Kshitiz; Kumar, Vijay
Abstract: Traditional and novel food processing methods has been employed to reduce the anti-nutritional factors (ANFs) such as phytic acid, trypsin inhibitors, tannins, saponins and oxalate to enhance the safety and quality of edible grains. Among these, microwave processing has advantage of being fast, consistent, safe, efficient, and green technology for the reduction of the ANFs. Microwave processing power and duration has significant effect on the inactivation of ANFs and needs to be critically evaluated for effective application on food grains. The reduction of heat labile ANFs by microwave heating is due to degradation by heat along with formation of insoluble complex. Pre-treatment such as soaking enhance their reduction through leaching and hydrolysis. The present review illustrates the mechanism, scope, application and future prospects of microwave processing to reduce the different ANFs present in food grains. Graphical abstract: Image 1 Highlights: Microwave processing reduces ANFs due to their heat-labile nature. Soaking enhances the reduction of ANFs through leaching and hydrolysis. 100% inactivation of trypsin inhibiter can be achieved by microwave processing. Microwave processing is more effective in reduction of oxalate than other methods. Thermal degradation of ANFs involves the hydrolysis of peptide bonds.